Answer:
(6, - 3 )
Step-by-step explanation:
Given the 2 equations
2x + 5y = - 3 → (1)
2x + 2y = 6 → (2)
Subtracting (1) from (2) term by term will eliminate the x- term
(2x - 2x) + (2y - 5y) = 6 - (- 3), that is
- 3y = 9 ( divide both sides by - 3 )
y = - 3
Substitute y = - 3 in either of the 2 equations and solve for x
Substituting y = - 3 in (1)
2x + 5(- 3) = - 3
2x - 15 = - 3 ( add 15 to both sides )
2x = 12 ( divide both sides by 2 )
x = 6
Solution is (6, - 3 )
Answer:
There is an inverse relationship between the total magnification and the diameter of the field of view – i.e., as magnifications increases the diameter of the field decreases in proportion, so the diameter of field of view at different magnification can be calculated mathematically, using the formula.
Step-by-step explanation:
Notice that the terms in parentheses on both sides of the equation are added to 4.
(3x + 4) + 4 = (5x - 4) + 4
So we can set the equation as.
3x + 4 = 5x - 4
Subtract 3x on both sides of equation.
4 = 2x - 4
Add 4 on both sides of equation.
8 = 2x
Divide both sides of equation by 2.
4 = x
4 is the only value that satisfies the statement.
Answer: financing a car
Step-by-step explanation:
i just took the apex test